Relationship between Socioeconomic Level, and the Prevalence of Masked Hypertension and Asymptomatic Organ Damage - Ateş, İhsan (Med Sci Monit, 2015)
BACKGROUND: This study aimed to determine the prevalence of masked hypertension (MHT) and its association with asymptomatic organ damage (AOD) in a low socioeconomic district of Ankara, Turkey. MATERIAL/METHODS: We retrospectively reviewed data obtained from the medical records of 712 patients with no known diagnosis of hypertension who presented to a polyclinic due to symptoms related to elevated blood pressure (BP) and were screened for MHT. Essential hypertension (EHT) existed in 86 patients screened for AOD. The presence of AOD in patients diagnosed with MHT and EHT was recorded. RESULTS: Among the 712 patients, 206 were diagnosed with EHT. Among the remaining 506 patients, 73 were diagnosed with MHT. The patients with MHT had significantly higher left ventricular mass index, carotid intima-media thickness, and 24-h urinary microalbuminuria level (all indicators of AOD) than those with EHT. CONCLUSIONS: A significantly higher percentage of patients with MHT had AOD, as compared to those with EHT, in a low socioeconomic district of Ankara. Based on this finding, patients who present with hypertensive symptoms but have a normal BP should be advised to measure their BP at home.